ENVIRONMENTAL PROBLEMS AND LAW ENFORCEMENT OF MANGROVE FORESTS IN THE JAKARTA COASTAL - Sri Suparni; Arman Syah Putra; Budhi Sriyono Prasetyo (Journal of Innovation Research and Knowledge, 2022)
The background of this research is how to solve an environmental problem, especially the law enforcement section in the coastal mangrove forest of Jakarta, legal protection for law enforcers in the environment. It has not been able to be overcome optimally, therefore legal certainty must be given in order to protect the environment by Therefore, this research is expected to be able to provide suggestions and contributions in order to assist law enforcement officers in carrying out their duties. The method used in this study is to use the literature review method by using the basics of thought based on journals that have been published on environmental journals and as a legal basis using environmental law. The problem raised in this research is how to find out environmental problems and law enforcement in Jakarta's coastal mangrove forests, knowing these problems can be improved So that the environment in Jakarta's coastal mangrove forests will be better. The purpose of this research is how to find problems that occur in environmental problems and law enforcement, especially in mangrove forests on the coast of Jakarta by knowing the problems will be able to correct deficiencies that occur in the field.